2012
DOI: 10.1210/en.2012-1127
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of Protein Kinase A Phosphorylation Sites in the Major Lipolytic Protein, Adipose Triglyceride Lipase

Abstract: Catecholamine-stimulated lipolysis occurs by activating adenylate cyclase and raising cAMP levels, thereby increasing protein kinase A (PKA) activity. This results in phosphorylation and modulated activity of several key lipolytic proteins. Adipose triglyceride lipase (ATGL) is the primary lipase for the initial step in triacylglycerol hydrolysis, and ATGL activity is increased during stimulated lipolysis. Here, we demonstrate that murine ATGL is phosphorylated by PKA at several serine residues in vitro and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 49 publications
2
102
2
1
Order By: Relevance
“…Given that PKA acts upstream from ATGL-1 and LID-1 in fasting-induced lipolysis, we asked the question whether PKA might directly phosphorylate ATGL-1 and/or LID-1. Recently, it has been demonstrated that mammalian ATGL is phosphorylated by PKA at multiple sites (55). In vitro kinase assays revealed that PKA phosphorylated C. elegans ATGL-1 but not LID-1 (data not shown).…”
Section: Atgl-1 As Shown Inmentioning
confidence: 90%
“…Given that PKA acts upstream from ATGL-1 and LID-1 in fasting-induced lipolysis, we asked the question whether PKA might directly phosphorylate ATGL-1 and/or LID-1. Recently, it has been demonstrated that mammalian ATGL is phosphorylated by PKA at multiple sites (55). In vitro kinase assays revealed that PKA phosphorylated C. elegans ATGL-1 but not LID-1 (data not shown).…”
Section: Atgl-1 As Shown Inmentioning
confidence: 90%
“…3C). PKA promotes lipolysis by phosphorylating several proteins including lipid droplet-associated protein perilipin A (Miyoshi et al 2007), hormone-sensitive lipase (HSL) (Krintel et al 2008), and adipose triglyceride lipase (ATGL) (Pagnon et al 2012). In normal fed condition, insulin promotes lipogenesis and suppresses lipolysis partially through inhibition of cAMP/PKA signaling by activation of PDE3B in adipocyte (Eriksson et al 1995, Kitamura et al 1999.…”
Section: Camp/pka In Adipose Tissuesmentioning
confidence: 99%
“…For instance, major components of lipolytic pathways, including hormone-sensitive lipase (Hsl) 2 and perilipin 1 (Plin1), are direct targets of PKA (10,11). Recently, adipose triglyceride lipase (Atgl) was also reported to be a target of PKA (12,13). Upon receiving activation signals from molecules such as catecholamine and glucagon, activated PKA phosphorylates Plin1 and HSL to promote the recruitment of HSL to lipid droplets (14,15).…”
mentioning
confidence: 99%